STUDY NOISE POLLUTION TYUMEN USING GIS - V. A. Dobryakova; A. A. Kolesov (InterCarto. InterGIS, 2016)
One of the most harmful factors of environment of the city is the noise, and its weight among the factors adversely affecting the life and health of the population has been increasing steadily [Sheina and etc., 2007; Polovinkina and etc., 2012]. Today, most major cities of the Russian Federation (70%) have a high noise pollution problem. The system of support for the monitoring and control of acoustic situation in the city can be considered noise pollution electronic cards made using geographic information systems (GIS). There are two fundamentally different approaches to the selection of software for creation of noise maps. According to the first of them, use universal multifunctional complexes GIS (ArcGIS, MapInfo). According to the distribution of data points on the noise characteristics is created TIN model. A second approach to create noise maps using highly specialized software (MapNoise, SoundPLAN, Mitha, Cadna, ExNOISE et al.). To calculate noise propagation area is divided on the grid with a certain step, the most relevant mapping purposes. Calculation of noise levels is carried out in a grid cell by measurements based on diffraction and reflection of sound barriers and absorbing underlying surface. Noise pollution is also displayed using contour lines.